USING PROBLEM-SOLVING METHODS TO TEACH SPEAKING TO B1 LEVEL LEARNERS - Botirkhujaeva Munisakhon Sherzod qizi, Javohir Abduvokhidov (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article explores the application of problem-solving methods as an effective strategy for enhancing speaking skills among B1 level English learners. It discusses how engaging students in real-life problem scenarios stimulates communication, critical thinking, and spontaneous language use. The author outlines several classroom techniques, such as role plays, debates, simulations, and collaborative tasks, which encourage learners to negotiate meaning and express ideas clearly. The article also emphasizes the importance of learner autonomy and interaction in promoting fluency and confidence. Through both theoretical insights and practical examples, the article demonstrates how problem-solving activities can foster a more dynamic and communicative learning environment for intermediate students.